2016
DOI: 10.1186/s41043-016-0068-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with compliance to recommended micronutrients uptake for prevention of anemia during pregnancy in urban, peri-urban, and rural communities in Southeast Nigeria

Abstract: BackgroundThe study investigated the factors associated with compliance to the recommended ≥90-day uptake of micronutrients for prevention of iron-deficiency anemia during pregnancy in Nigeria.MethodsA cross-sectional study of 1500 women who had babies within 6 months prior to the survey, drawn from six urban, peri-urban, and rural local government areas in Enugu and Imo States of Nigeria, was conducted, using a structured questionnaire. A focus group discussion was held with grandmothers and fathers of the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 39 publications
2
11
1
Order By: Relevance
“…Other studies have indicated that women with high wealth quintile and eating three and above meals per day were likely to adhere to IFAS compare to women from low wealth quintile [36,37]. However, in the present study, women from the families eating twice or less were found to be 3.4 times more likely to adhere to IFAS as compared to women from the families who ate three times and more.…”
Section: International Journal Of Reproductive Medicinecontrasting
confidence: 85%
See 1 more Smart Citation
“…Other studies have indicated that women with high wealth quintile and eating three and above meals per day were likely to adhere to IFAS compare to women from low wealth quintile [36,37]. However, in the present study, women from the families eating twice or less were found to be 3.4 times more likely to adhere to IFAS as compared to women from the families who ate three times and more.…”
Section: International Journal Of Reproductive Medicinecontrasting
confidence: 85%
“…Women living 60 minutes or more from the health facilities were less likely to adhere to the IFAS program 0.34 times compared to the women living near the health facilities. In other studies, women who were living close to health facilities or private pharmacies had more chance to adhere to the IFAS program more times compared to women who were living far from health facilities [25,36,40]. The reasons might be the lack of close health facilities and less economic index; less availability of pharmacies used to sell IFAS and negligence among mothers were the reasons for low adherence to the IFAS program.…”
Section: International Journal Of Reproductive Medicinementioning
confidence: 86%
“…Improving continued access to supplements throughout pregnancy is also a priority as fewer prenatal visits are associated with a lower number of IFA tablets consumed (Lutsey et al, ; Onyeneho et al, ; Sununtnasuk et al, ). In Vietnam, the most important factor enabling taking iron tablets for at least 5–9 months was a frequent supply of iron tablets (Aikawa et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The behaviour, attitudes and perceptions of the pregnant women determine the outcome of iron supplementation programmes (Kamau, Mirie, and Kimani 2018;Nisar et al 2014;Dwumfour-Asare and Kwapong 2013;Najafi, Roudsari, and Hejazi 2013). Some pregnant women may not want to take the tablets and their attitudes may be influenced by ethnicity, myths and truths derived from their culture and religion, previous side effects experienced, and levels of knowledge acquired (Kamau, Mirie, and Kimani 2018;Onyeneho et al 2016;Nisar et al 2014;Dwumfour-Asare and Kwapong 2013;Najafi, Roudsari, and Hejazi 2013).…”
Section: Figurementioning
confidence: 99%